(3YHK GdhdjO aj GdcdGe Ydi TYQ CHj oYHGOI GdhdjOs - (3CMeO Hf YHO Gddg Hf SdjeGf GdJfhNj , CHh GdYdGA GdeYQj , J (B449 (3g` s; (3GdHMJQj , CHh YHGOI GdhdjO Hf YHjO Hf jMji GdWGFj GdHMJQj, GdHMJQj,J (B284 (3g` s
(3ChdgG (B:s
(3KHJ aj OjhGf GdHMJQj eeG CUdM ef GdZdW s
(3BNQgG (B:s
(3hcPdc GdbWYI GdJj ChdgG(B: (3SQi GdZeGe hYGOJfG ZhGOjg s
(3HChdgG JedjcGJ hhba CbOegG SfI (B1099(3g`s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B9 - (3U (B141s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B26 s
Keywords: (3GdCOHs